Expression of VEGF in peripheral serum is a possible prognostic factor in bone-regeneration via Masquelet-technique: a pilot study - Tanner, Michael Christopher; Boxriker, Sonja; Haubruck, Patrick; Child, Christopher; Westhauser, Fabian; Fischer, Christian; Schmidmaier, Gerhard; Moghaddam-Alvandi, Arash (Journal of Clinical Medicine, 2021)
Two-step Masquelet-technique established a new procedure in the treatment of osseous defects, addressing prerequisites postulated by the “diamond concept”. Increase in blood perfusion and growth factors are enhanced by the “Masquelet-membrane”. To describe this, we measured serum levels of Vascular Endothelial Growth Factor (VEGF) of patients with atrophic non-unions of long bones undergoing Masquelet-technique. From over 500 non-union patients undergoing Masquelet-technique with prospective follow-up we randomly selected 30 patients. 23 were included, 7 lost to follow-up or excluded because of incomplete data. Serum was drawn at specified intervals before and after surgery. Patients were followed for at least 6 months after step 2. Classification into both groups was performed according to radiological results and clinical outcome 6 months after step 2. Concentration of VEGF in patients’ serum was performed via ELISA. 14 achieved osseous consolidation (responder group), 9 cases did not (non-responder). Responders showed a significant increase of serum-VEGF in the first and second week when compared to the preoperative values of step 1. Non-responders showed a significant increase of VEGF in the second week after Steps 1 and 2. Comparison of groups showed significantly higher increase of serum-VEGF week2 after step 1 and preoperative to step 2 for responders. Results show one possibility of illustrating therapeutic progress by monitoring growth factors and possibly allowing prognostic conclusions thereof. This might lead to a more targeted treatment protocol.
Gesehen am 10.09.2021